2021
DOI: 10.1183/13993003.04099-2020
|View full text |Cite
|
Sign up to set email alerts
|

Breathlessness in COPD: linking symptom clusters with brain activity

Abstract: RationaleCurrent models of breathlessness often fail to explain disparities between patients' experiences of breathlessness and objective measures of lung function. While a mechanistic understanding of this discordance has thus far remained elusive, factors such as mood, attention and expectation have all been implicated as important modulators of breathlessness. Therefore, we have developed a model to better understand the relationships between these factors using unsupervised machine learning techniques. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…Mood and physical fatigue appear to be important perceptual modulators impacting individuals' symptom reporting (Finnegan et al, 2021 ; Harrison et al, 2021c ), therefore, we investigated the impact of these factors on AMS symptom burden in our cohort with hierarchical cluster analysis. Average Lake Louise AMS score over the trek clustered with self-reported measures of anxiety, agoraphobia, and neuroticism taken at sea level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mood and physical fatigue appear to be important perceptual modulators impacting individuals' symptom reporting (Finnegan et al, 2021 ; Harrison et al, 2021c ), therefore, we investigated the impact of these factors on AMS symptom burden in our cohort with hierarchical cluster analysis. Average Lake Louise AMS score over the trek clustered with self-reported measures of anxiety, agoraphobia, and neuroticism taken at sea level.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, fatigue and anxiety may be the brain's manifestations of poor perceived self-efficacy and control, presenting as a state of learned helplessness (Stephan et al, 2016 ). Indeed, 1 study of breathlessness in 100 patients with Chronic Obstructive Pulmonary Disease demonstrated different behavioral profiles and brain activity in the anterior insula (a likely key interoceptive center) between a high and low symptom burden group, in the absence of any differences in spirometry between the two groups (Finnegan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence [13, 5, 9, 11, 2528] now suggests that breathlessness, far from simply arising as a product of peripheral inputs, includes steps of active interpretation and comparison with previously held expectations. In this study we demonstrated that as the observed VR hill gradient increased, participants’ reported breathlessness was also increased, independent of the physical effort applied to pedalling the bike.…”
Section: Discussionmentioning
confidence: 99%
“…Mood and physical fatigue appear to be important perceptual modulators impacting individuals’ symptom reporting (Harrison et al, 2020b; Finnegan et al, 2021), therefore we investigated the impact of these factors on AMS symptom burden in our cohort with hierarchical cluster analysis. Average Lake Louise AMS score over the trek clustered with self-reported measures of anxiety, agoraphobia, and neuroticism taken at sea level.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, fatigue and anxiety may be the brain’s manifestations of poor perceived self-efficacy and control, presenting as a state of learned helplessness (Stephan et al, 2016). Indeed, one study of breathlessness in 100 patients with Chronic Obstructive Pulmonary Disease demonstrated different behavioural profiles and brain activity in the anterior insula (a likely key interoceptive centre) between a high and low symptom burden group, in the absence of any differences in spirometry between the two groups (Finnegan et al, 2021). Therefore, we also hypothesised that self-report questionnaires characterising individuals’ baseline psychological state may correlate with their symptom burden over the expedition.…”
Section: Introductionmentioning
confidence: 99%